Risk of adverse outcomes in offspring with RT-PCR confirmed prenatal Zika virus exposure: an individual participant data meta-analysis of 13 cohorts in the Zika Brazilian cohorts consortium - Ximenes, Ricardo Arraes de Alencar (2023)
Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq). Wellcome Trust and the United Kingdom’s Department for International Development. European Union’s Horizon 2020 research and innovation program. Medical Research Council on behalf of the Newton Fund and Wellcome Trust. National Institutes of Health/National Institute of Allergy and Infectious Diseases. Foundation Christophe et Rodolphe Mérieux. Coordenação de perfeiçoamento de Pessoal de Nível Superior (Capes). Ministério da Saúde do Brasil. Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP). Fundação de Amparo à Pesquisa do Estado do Rio de Janeiro (FAPERJ). Instituto Evandro Chagas/Ministério da Saúde. Fundação de Amparo à Pesquisa do Estado de Goiás (FAPEG). Fundação de Amparo à Pesquisa do Estado do Rio Grande do Sul (FAPERGS). Fundação de Apoio ao Ensino, Pesquisa e Assistência do Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto. Secretaria de Saúde do Estado de São Paulo. Fundação de Amparo à Ciência e Tecnologia de Pernambuco (FACEPE).